2016
DOI: 10.5530/jyp.2016.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Experimentation on Hibiscus rosa Flower Mucilage as a Potential Nasal Mucoadhesive its Characterization as an In-situ Gel for some Anxiolytics

Abstract: Objective: The objective of the present study was to prepare mucoadhesive in situ nasal gels with mucilage isolated from hibiscus flower (Hibiscus rosa sinensis, family: malveceae) containing alprazolam. Methods-Nasal gels of alprazolam were prepared using three different concentration (0.5%, 1% and 1.5% w/v) of H Rosa mucilage (HRM) and synthetic polymers (Hydroxy propyl methyl cellulose and carbopol 934). In situ gels were prepared with mixture of pluronic F127 and mucoadhesive agent. Result: Evaluation of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The pH of HRS mucilage is generally 6.2, which is nearly neutral [17,18,20] and therefore will not irritate the mucosal membranes of the body. Drug-excipient compatibility studies have shown no significant interactions [6,[21][22][23], indicating that HRS mucilage can be used for a wide range of drugs.…”
Section: Hrs Mucilage In Pharmaceutical Dosage Forms and Drug Deliver...mentioning
confidence: 99%
See 3 more Smart Citations
“…The pH of HRS mucilage is generally 6.2, which is nearly neutral [17,18,20] and therefore will not irritate the mucosal membranes of the body. Drug-excipient compatibility studies have shown no significant interactions [6,[21][22][23], indicating that HRS mucilage can be used for a wide range of drugs.…”
Section: Hrs Mucilage In Pharmaceutical Dosage Forms and Drug Deliver...mentioning
confidence: 99%
“…Roy et al [23] developed an in-situ nasal gel from HRS mucilage, using alprazolam as a model drug. In comparison to carbopol and hydroxypropyl methylcellulose (HPMC), HRS mucilage demonstrated superior bioadhesion to the nasal membrane due to its moderate swelling.…”
Section: Gelling Agent In Gel Dosage Formsmentioning
confidence: 99%
See 2 more Smart Citations